(untitled) (Academic Journal of Internal Affairs, 2025)
Aim: In the recent past multiple changes went through which had an effect not only on the international politics but also on Hungary impacting the both legal and illegal migration which goes through Europe. Methodology: All of this justifies the review of current tendencies by analysing current trends in refugee management and their international effects. Findings: In that changed international environment migration has become even more complex and gained even more latency, and beside that it has also become a viable instrument for state’s hybrid warfare activity. Value: Knowledge of the current international impact mechanism of the active migration dynamics calls for consideration and the earliest possible harmonization of the rather heterogeneous present asylum policies of the Member States and the EU.